STRUCTURAL GAPS IN NAZHIR REMUNERATION: COMPARING THE LEGAL FRAMEWORKS AND WAQF GOVERNANCE IN INDONESIA AND BRUNEI DARUSSALAM - Siska Lis Sulistiani; Intan Nurrachmi; Ramdan Fawzi; Abdurahman Raden Aji Haqqi (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2026)
Purpose – This study aims to analyze the legal basis, forms, and mechanisms of waqf administrator remuneration in Indonesia and Brunei Darussalam, and to evaluate their differences through the perspective of maqāṣid al-sharī‘ah to identify potential structural remuneration gaps. Scholarly attention to the relationship between remuneration frameworks and Waqf institutional sustainability remains limited. Methods – This study employs a comparative legal method based on library research. Primary sources include legislation and official institutional documents from Indonesia and Brunei Darussalam, while secondary and tertiary sources comprise relevant scholarly literature. The comparative analysis focuses on the allocation of waqf management responsibilities, the legal basis for remuneration or financial support, and their relationship to the protection and productive development of waqf assets, evaluated through the principles of maqāṣid al-sharī‘ah. Findings – Indonesia and Brunei Darussalam regulate waqf administration through distinct legal and institutional frameworks. In Indonesia, Nazhir may receive remuneration from the net proceeds of waqf management and development, capped at 10 percent under Article 12 of Law No. 41 of 2004, thereby linking compensation to asset-management performance. In Brunei Darussalam, waqf administration falls under the authority of the Majlis Ugama Islam Brunei (MUIB) within a centralised institutional framework, without an equivalent statutory formula for individual remuneration. This difference reveals a structural gap in the legal basis, compensation mechanisms, and allocation of institutional responsibility. From a maqāṣid al-sharī‘ah perspective, both models seek to protect waqf assets (ḥifẓ al-māl) and sustain their public benefits but require the integration of professional incentives, performance accountability, institutional oversight, and asset protection to ensure sustainable waqf management. Contribution and Limitations – This study contributes to waqf governance scholarship by offering a comparative framework for understanding the relationship between remuneration regulation, professionalisation of waqf administrators, and protection of waqf assets. Its limitation lies in its focus on legal and institutional dimensions, based primarily on library sources and official documents. Originality/value – This study conceptualises the remuneration gap as a structural disparity in the legal basis, compensation mechanisms, institutional responsibilities, and relationship between remuneration and waqf management performance.